METABOLIC AND VASCULAR FEATURES OF DYNAMIC CONTRAST ENHANCED BREAST MRI AND (15)O-WATER PET BLOOD FLOW IN BREAST CANCER - Eby, Peter R. (2008)
RATIONALE AND OBJECTIVES: To (1) describe associations between measures of tumor perfusion by dynamic contrast-enhanced breast MRI (DCE-MRI), blood flow by (15)O-water PET and metabolism by (18)F-FDG PET and (2) improve our understanding of tumor enhancement on MRI through independent measures of tumor metabolism and blood flow. MATERIALS AND METHODS: We performed a retrospective analysis of the existing PET and MRI databases from the departments of Nuclear Medicine and Radiology. We identified patients with locally advanced breast cancer who underwent (15)O-water/(18)F-FDG PET within 1 month of clinical DCE-MRI between February 2004 and August 2006. The (15)O-water PET blood flow and (18)F-FDG metabolic rate (MR) and tissue transport constant (K(1)) in the primary malignancy were calculated. DCE-MRI peak percent enhancement (PE) and peak signal enhancement ratio (SER) were measured for each tumor. Correlations and regression analysis of these variables were performed. RESULTS: Fifteen patients with complete PET and DCE-MRI data were included in the analysis cohort. Peak SER correlated significantly with blood flow (r=0.73, p=0.002) and K(1) (r=0.76, p=0.001). However, peak SER did not correlate significantly with FDG MR (r=0.44, p=0.101). There were no significant correlations between peak PE and any of the PET parameters. CONCLUSIONS: Our findings suggest that tumor perfusion, represented by (15)O-water PET blood flow, is an important factor in the MRI enhancement of LABC. A lack of correlation of FDG MR with blood flow and DCE-MRI kinetics suggests that (18)F-FDG PET provides complementary metabolic information independent of vascular factors.